Effects of dietary grape seed polyphenols supplementation during late gestation and lactation on antioxidant status in serum and immunoglobulin content in colostrum of multiparous sows1. (20th April 2019) - Wang, Xiangrong; Jiang, Guitao; Kebreab, Ermias; Yu, Qifang; Li, Jinghui; Zhang, Xu; He, He; Fang, Rejun; Dai, Qiuzhong
Abstract: The aim of this study was to determine the effects of dietary grape seed polyphenols (GSP ) supplementation during the late gestation and lactation period on reproductive performance, antioxidative status in serum, nutrient composition, and Ig content in colostrum of multiparous sows. On day 80 of gestation, a total of 64 sows with similar body condition were allocated to a completely randomized block design with 4 dietary treatments ( n = 16 sows per treatment): 1) basal diet (CON, control group); 2) basal diet supplemented with 200 IU/kg vitamin E (200VE, positive control group); 3) basal diet supplemented with 200 mg/kg GSP (200GSP ); and 4) basal diet supplemented with 300 mg/kg GSP (300GSP ). The trial lasted 56 d until the piglets were weaned on day 21 of lactation. Reproductive performance, parameters of antioxidative status, and levels of progesterone (P4 ) and estradiol (E2 ) in serum, nutrient composition, and Ig content in colostrum of sows were determined. The number of dead fetuses was reduced, and farrowing survival was significantly improved in the litters from 300GSP-fed ( P < 0.05). Preweaning survivability significantly increased in the litters from sows fed 200GSP and 200VE ( P < 0.05). The activity of superoxide dismutase and glutathione peroxidase (GSH-Px ) in the serum was significantly increased in sows fed 200GSP and 300GSP ( P < 0.05). The activity of GSH-Px in the serum also significantly increased in sows fed 200VE ( P < 0.05). Sows fed 300GSP had the greatest levels of P4 and E2 in the serum, which was significantly greater than sows fed 200VE and CON ( P < 0.05). No significant differences were found among treatments for the content of solids-not-fat, fat, protein, and lactose in colostrum ( P > 0.05). However, sows fed GSP had greater IgM and IgG content in colostrum compared with sows fed 200VE and CON ( P < 0.05). In conclusion, dietary GSP supplementation during late gestation and lactation improved the farrowing survival and preweaning survivability, enhanced the antioxidant status and hormone levels in serum, and increased the IgM and IgG content in colostrum of sows.